Who Convened the First Council of Nicaea: Constantine or Ossius? - Fernández Eyzaguirre, Samuel (The journal of theological studies, 2020)
The ancient church historians affirmed that it was Constantine himself who convened the Council of Nicaea. However, a chronological examination of the contemporary documents shows that the convocation of Nicaea was quite different. This essay aims to examine the origin of the idea of holding the Nicene council. According to the available data, Ossius of Cordoba convened the great episcopal council that was to be held at Ancyra but ultimately occurred in Nicaea. Although Constantine’s participation was decisive for the success of Nicaea, the study of the historical sources indicates that the original idea of holding the council that ultimately occurred at Nicaea must be credited to Ossius.